Synthesis, crystal structure, DFT analysis, and DNA studies of a binuclear copper(II) complex with 2, 2′-bipyridine and 4-aminobenzoate. Issue 16 (17th December 2021) - Parthiban, D.; Baskaran, S.; Rani, S.; Arumugham, M.N.; Si, N. T.; Kumar, R.
Abstract: A complex containing two discrete molecules, [Cu2 (bpy)2 (4-Ab)2 (NO3 )(H2 O)] and [Cu2 (bpy)2 (4-Ab)2 (H2 O)2 ] and the lattice including three NO3 anions, one 4-Ab, and three H2 O molecules (bpy = 2, 2′-bipyridine, 4-Ab = 4-aminobenzoate), was prepared and structurally determined using elemental analyses, IR, EPR, UV-visible, and single-crystal X-ray crystallography. X-ray single-crystal structural studies indicated that the [Cu2 (bpy)2 (4-Ab)2 ] unit was present in both the crystallographic units. The complex crystallized in an orthorhombic crystal system with space group Pna21, a = 35.004(3) Å, b = 18.4134(16) Å and c = 12.8659(12) Å. In both crystallographic units, the geometry of the Cu(II) ions is distorted square-pyramidal, where both nitrogen atoms from one bpy and two oxygen atoms from two different p-aminobenzoate ions constitute the square plane and the apical positions are occupied by solvent or nitrate oxygen atoms. The geometry optimization of both units of the binuclear complex was carried out by taking the coordinates of the respective X-ray structures using DFT. The binding studies of the copper(II) complex with calf thymus DNA (CT-DNA) were explored by UV-Vis absorption, fluorescence spectroscopic, and cyclic voltammetric techniques. Also, the cleavage of pBR322 DNA with the binuclear copper(II) complex was studied using the gel electrophoresis method. Graphical Abstract: UF0001